Children's Mental Health: A Scientific Application and Cultural Values in Daily Lives - Saputra, Dwijo (Faculty of Psychology, Universitas Surabaya, 2011)
In the last two decades, a variety of results of scientific verification related to the development ofpsychopathology or therapy methods have been obtained, including psychosocial or medica-mentous therapies for various types of emotional and behavioral disorders in children andadolescents. Children's and adolescents' daily mental health services play very important roles inchildren's development in order to reach optimum development. In order that results andeffective and efficient benefits can be rendered, mental health services for children and adoles-cents must be done by considering results of empirical researches. Nevertheless, in its appli-cation, one must consider the heterogeneity of the population in the service center, including theconditions of the children and adolescents requiring help, the personnel of the health servicecenter, ethics and cultural values; and available service system. Dalam dua dekade terakhir didapatkan berbagai hasil pembuktian ilmiah yang berkaitan denganperkembangan terjadinya gangguan kesehatan jiwa (psikopatologi) maupun metode terapi.Metode meliputi terapi psikososial maupun terapi medikamentosa bagi berbagai kondisigangguan emosi dan perilaku pada anak dan remaja. Layanan kesehatan jiwa anak dan remajadalam praktik sehari hari adalah layanan yang memiliki peran sangat penting bagi perkembangananak, agar setiap anak dimungkinkan untuk mencapai perkembangan yang seoptimal mungkin.Agar dapat memberikan hasil dan manfaat yang efektif dan efisien, pemberian layanankesehatan jiwa bagi anak dan remaja harus dilakukan dengan mempertimbangkan hasilpenelitian secara empiris. Namun, dalam penerapannya harus dipertimbangkan heterogenitaspopulasi di tempat pelayanan, termasuk kondisi anak dan remaja yang memerlukan bantuan,orang yang memberi pelayanan, etika dan nilai budaya, dan sistem pelayanan yang tersedia.